BUILDING AND STANDARDIZING A TEST TO MEASURE MUSCULAR STRENGTH AND DYNAMIC BALANCE DURING ROTATION AND THEIR RELATIONSHIP TO THE DIGITAL PERFORMANCE LEVEL OF YOUNG HAMMER THROWERS - Mahdi Lafta Rahi (Universitas Negeri Jakarta, 2025)
Background. The problem of this study lies in the urgent need for a standardized test that measures muscular strength and dynamic balance during rotation in a manner that realistically simulates the actual performance of the hammer throw. Most of the currently available tests measure these physical attributes separately and do not accurately reflect the complex, integrated nature of performance required in this event. Objectives. This study aimed to develop and standardize a test to measure muscular strength and dynamic balance during rotation among young hammer throwers and to identify their relationship to performance achievement. Method. The researcher used the descriptive method on a sample of (35) young hammer throwers aged (18–23 years) in Iraq. The proposed test consisted of performing three rotational turns inside the throwing circle using a 5 kg medicine ball, then throwing it with maximum force while maintaining balance. The analysis was assisted using the SPSS 26 application. Results. The results showed that the test demonstrated high scientific validity indicators: validity (0.89), reliability (0.91), and objectivity (0.95). Moreover, a very strong correlation (r = 0.89) was found between the test and the digital performance level, explaining 79% of the variance in achievement — a higher percentage compared to traditional tests. Six standard levels were established, ranging from Poor to Excellent. Conclusion. The researcher recommended using the test in selection and evaluation processes and emphasized integrating strength and balance training in athletic training programs. Integrating strength and balance into a single test is more effective than measuring them separately, as muscular strength and dynamic balance interact to determine performance level.